2016
DOI: 10.1186/s12981-016-0107-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV and hepatitis B coinfection in Ghana: a systematic review and meta-analysis

Abstract: BackgroundHuman immunodeficiency virus (HIV) and hepatitis B virus (HBV) coinfection has been associated with higher morbidity and mortality and may impact significantly on healthcare resource utilization. However, in Ghana, accurate estimates of the prevalence of HIV/HBV coinfection needed to inform policy decisions and the design of public health interventions are currently lacking. In this study, our aim was to determine the HIV/HBV coinfection prevalence rate in Ghana.MethodsPrimary studies reporting preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 34 publications
5
51
2
Order By: Relevance
“…Maternal complications due to HBV and HIV co-infection pose significant threat to the survival of both the mother and unborn child. On the other hand, in a low-resourced country such as Nigeria, the economic cost attributable to the impact of HIV and HBV coinfection has been well documented both at the microeconomic (individual) and the macroeconomic (household and population) levels [9]. In addition, a major epidemiologic implication is the increasing probability of dual transmission of new HBV/HIV infections in a mixed setting creating new chimeric recombinant forms (hitherto unknown) which may even pose a greater threat than the two separate epidemics.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal complications due to HBV and HIV co-infection pose significant threat to the survival of both the mother and unborn child. On the other hand, in a low-resourced country such as Nigeria, the economic cost attributable to the impact of HIV and HBV coinfection has been well documented both at the microeconomic (individual) and the macroeconomic (household and population) levels [9]. In addition, a major epidemiologic implication is the increasing probability of dual transmission of new HBV/HIV infections in a mixed setting creating new chimeric recombinant forms (hitherto unknown) which may even pose a greater threat than the two separate epidemics.…”
Section: Introductionmentioning
confidence: 99%
“…A true prevalence of these coinfections is essential for evidence based policy making and resource allocation and planning regarding cost effective interventions especially in a context of limited resources. This will positively impact on general prevention and treatment strategies as in HBV/HIV where ART agents also possess anti HBV activity [16] and the increasing availability of affordable generic Direct acting antivirals (DAA) for HCV treatment. The objectives of this study were to determine the sero-prevalence and correlates of Hepatitis B surface antigen (HBsAg) and anti HCV positivity in HIV/AIDS patients in a regional hospital setting in Cameroon.…”
Section: Introductionmentioning
confidence: 99%
“…5%], those with no history of blood transfusion and those with no history of alcohol intake. Pennap et al [16] in Nigeria, KouassiM'Bengue et al [12] in Cote d'voire and Agyeman and Ofori-Asenso, [17] in Ghana reported same in a similar study.…”
Section: Discussionmentioning
confidence: 54%